PENGARUH GREEN ACCOUNTING, DIVERSIFIKASI BISNIS, DAN MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2022–2024 - Astri Natalia Hutauruk; Harti Budi Yanti (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to examine the effect of green accounting, business diversification, and intellectual capital on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. A quantitative approach was employed using secondary data collected from annual reports and sustainability reports published by the companies. The data were analyzed using the EViews software with multiple linear regression methods. The results indicate that green accounting and intellectual capital have a significant positive influence on financial performance, while business diversification does not significantly affect financial performance. These findings imply that sustainability practices and effective intellectual capital management are essential factors in enhancing the financial performance of manufacturing firms in the era of the green economy. The study highlights the importance of adopting environmentally responsible accounting practices and leveraging intangible assets such as knowledge, skills, and innovation to create competitive advantages. Furthermore, the non-significant impact of business diversification suggests that expanding into multiple business areas without strategic alignment may not yield financial benefits. The implications of this research are crucial for policymakers, managers, and investors in emphasizing the role of sustainability and intellectual capital in financial decision- making. Future research is recommended to include other variables such as corporate governance, firm size, and industry type to enrich the model and provide broader insights. The study contributes to the growing body of literature on green finance and sustainability reporting in emerging markets, particularly in Indonesia’s dynamic manufacturing sector.